2014
DOI: 10.1111/jth.12738
|View full text |Cite
|
Sign up to set email alerts
|

Stalled cerebral capillary blood flow in mouse models of essential thrombocythemia and polycythemia vera revealed by in vivo two‐photon imaging

Abstract: To cite this article: Santisakultarm TP, Paduano CQ, Stokol T, Southard TL, Nishimura N, Skoda RC, Olbricht WL, Schafer AI, Silver RT, Schaffer CB. Stalled cerebral capillary blood flow in mouse models of essential thrombocythemia and polycythemia vera revealed by in vivo two-photon imaging. J Thromb Haemost 2014; 12: 2120-30.Summary. Background: Essential thrombocythemia (ET) and polycythemia vera (PV) are myeloproliferative neoplasms (MPNs) that share the JAK2 V617F mutation in hematopoietic stem cells, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 60 publications
(72 reference statements)
4
67
0
Order By: Relevance
“…Recent studies have revealed the significance of capillary stalling in aging, stroke, Alzheimer's disease, polycythemia and thrombocythemia 3,4,5,6,11,21,22,23 . In fact, capillary stalling largely impacts on CBF, and cognitive functions can be improved by suppressing capillary stalling in Alzheimer's disease 6,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the significance of capillary stalling in aging, stroke, Alzheimer's disease, polycythemia and thrombocythemia 3,4,5,6,11,21,22,23 . In fact, capillary stalling largely impacts on CBF, and cognitive functions can be improved by suppressing capillary stalling in Alzheimer's disease 6,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mice with polycythemia and thrombocytosis, two‐photon fluorescence microscopy has shown increased rates of stalled capillary blood flow in brain capillaries compared to control mice (Santisakultarm et al. ), and fluorescein angiography of retinal vessels in patients with PV has shown qualitatively reduced retinal and choroidal blood flow as compared with controls (Yang et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Branch order was determined by running multiple loops to assign first branch order to capillaries stemming from penetrating arterioles, followed by the subsequent connecting capillaries branches until the segments merged with ascending venules. Identification of stalled capillaries was performed as previously described (Santisakultarm et al, 2014). RBC flow speed and vascular diameter of arteriole, venule, and capillary vessels were measured using previously published methods (Hall et al, 2014; Santisakultarm et al, 2012) with minor modifications (Drew et al, 2011).…”
Section: Methodsmentioning
confidence: 99%